The Influence of Physical Activity on Inflammatory Markers, Intestinal Microbiota Composition and Disease Activity in Inflammatory Bowel Disease - Paulina Jakubczyk; Piotr Widera; Justyna Helis; Maciej Michalik; Aleksandra Buczek; Hubert Bigajski; Aleksandra Banaś; Olga Bilczewska; Wiktoria Janik; Marta Handschuh (Quality in Sport)
Aim of the Study This review investigates the relationship between physical activity and inflammatory bowel disease (IBD), focusing on inflammatory markers, gut microbiota composition, and disease activity. The objective is to examine how exercise intensities influence inflammation, microbial diversity, and patient outcomes for IBD management.